Ab initio study of lattice instabilities of zinc chalcogenides ZnX (X=O, S, Se, Te) induced by ultrafast intense laser irradiation - Dahua Ren (AIP Advances, 2017)
Ab initio calculations of lattice constants, lattice stabilities of ZnX (X=O, S, Se, Te) at different electronic temperatures (Te) have been performed using generalized gradient approximation (GGA) pseudopotential method within the density functional theory (DFT). The calculated phonon frequencies of ZnX at Te = 0 eV accord well with the experimental and other theoretical values. Firstly, it is indicated that the lattice constants of ZnX increase and all the phonon frequencies reduce as Te increases. Additionally, the transverse-acoustic phonon frequencies of ZnX are imaginary with the elevation of Te, namely the lattices of ZnX become unstable under ultrafast intense laser irradiation. Moreover, the transverse optical mode-longitudinal optical mode (LO-TO) splitting degree of ZnX (X=S, Se, Te) gradually decreases as the electronic temperature increases, mainly due to the reason that the electronic excitation weakens the strength ionicity of ionic crystal ZnX under intense laser irradiation. However, the LO-TO splitting degree of ZnO firstly increases and then decreases with the increase of electronic temperature. After that, it can be helpful for understanding the mechanism of ultrafast intense laser induced semiconductors damage.